* Your assessment is very important for improving the workof artificial intelligence, which forms the content of this project
Download Induction
List of first-order theories wikipedia , lookup
Philosophy of mathematics wikipedia , lookup
List of important publications in mathematics wikipedia , lookup
Foundations of mathematics wikipedia , lookup
Georg Cantor's first set theory article wikipedia , lookup
Laws of Form wikipedia , lookup
Gödel's incompleteness theorems wikipedia , lookup
Four color theorem wikipedia , lookup
Fundamental theorem of calculus wikipedia , lookup
Fermat's Last Theorem wikipedia , lookup
Wiles's proof of Fermat's Last Theorem wikipedia , lookup
Peano axioms wikipedia , lookup
Principia Mathematica wikipedia , lookup
Brouwer–Hilbert controversy wikipedia , lookup
Fundamental theorem of algebra wikipedia , lookup
Chapter 3 Induction In this chapter we learn a way to prove a statement of the form (∀n ∈ N)P (n). For example, suppose we were adding even natural numbers and we detected a pattern. That is, 2 2+4 = = 2+4+6 = .. . 1·2 2·3 3·4 So we conjecture 2 + 4 + · · · + 2n = n · (n + 1) for all n. How do we prove this when we cannot check the statement for every n ∈ N? Here is a way to do it. Suppose we prove the statement P (1). Then we prove the connective statement P (n) → P (n + 1) is true for each n ∈ N. That is, we assume P (n) is true and we show P (n + 1) follows. Then, since P (1) is true and P (1) → P (2), P (2) is true, and in the same way P (3) is true and so on. A bit like dominos falling. This method of proof is called the Principle of Mathematical Induction. More formally, Theorem 3.1. (Principle of Mathematical Induction) Suppose P (n) is a statement for each n ∈ N. Moreover, suppose (i) Base Step: P (1) is true. (ii) Inductive Step: for each n ∈ N, P (n) implies P (n + 1). Then P (n) is true for all n ∈ N. We will prove the theorem below. The proof will require a further assumption about the natural numbers. 29 30 3. Induction Example 3.2. Prove 2 + 4 + · · · + 2n = n · (n + 1) for all n ∈ N. Proof. Let P (n) be the statement 2 + 4 + · · · + 2n = n · (n + 1). (i) Base Step: the statement P (1) is 2 = 1 · 2 which is obviously true. (ii) Inductive Step: suppose 2 + 4 + · · · + 2n = n · n(n + 1). Adding 2(n + 1) to both sides gives 2 + 4 + · · · + 2n + 2(n + 1) = = n(n + 1) + 2(n + 1) (n + 1)(n + 2). This is P (n+1). Thus, by the Principle of Mathematical Induction, 2+4+· · ·+2n = n · (n + 1) for all n ∈ N A strategy for proving the inductive step is to write down, in the scratch area, the statement P (n + 1). When P (n) involves an equality or an inequality. Pick a side (left or right) and manipulate it to look like the same side of P (n + 1). Finally manipulate the other side to make it look like the corresponding side of P (n + 1). We illustrate this in the next example. Example 3.3. Prove 2n−1 ≤ n!, where n! = n(n − 1)(n − 2) · · · 1. Scratch Work. We can easily check P (1). The difficult part is showing P (n) → P (n + 1). The statement P (n + 1) is the statement 2n ≤ (n + 1)!, and, again, we need to derive this from 2n−1 ≤ n!. Following the above suggestion we multiply P (n) by 2 to make the left side of P (n) look like the left side of P (n + 1). Then we deal with the right side. We find 2 2n−1 ≤ 2n!. That is, 2n ≤ 2n!. Since 2 ≤ n + 1 for n ≥ 1, we get 2n ≤ (n + 1)n! or 2n ≤ (n + 1)!. This is P (n+ 1). In the proof below we work with the right side-just to be different. Proof. Let P (n) be the statement 2n−1 ≤ n!. (i) Base Step: P (1) is 20 ≤ 1 or 1 ≤ 1 which is true. (ii) Inductive Step: Suppose P (n) is true for all n ∈ N. That is, suppose 2n−1 ≤ n!. Multiplying both sides by n + 1, we find (n + 1)2n−1 ≤ (n + 1)n! = (n + 1)!. Moreover, we have 2 ≤ n + 1 for all n ∈ N. Hence, 2 2n−1 ≤ (n + 1)2n−1 ≤ (n + 1)!. That is, 2n ≤ (n + 1)!. This is P (n + 1). The result follows from the Principle of Mathematical Induction. Example 3.4. Suppose x, y ∈ R and 0 < x ≤ y. Then xn ≤ y n for all n ∈ N. Proof. Let P (n) be the statement xn ≤ y n . (i) Base Step: P (1) is x ≤ y which by assumption is true. (ii) Inductive Step: Suppose 0 < xn ≤ y n . Multiplying both sides by x, we find xn+1 ≤ xy n . Since x ≤ y, we have xn+1 ≤ xy n ≤ y y n = y n+1 . That is, 0 < xn+1 ≤ y n+1 . This is P (n + 1). 31 3. Induction The result follows from the Principle of Mathematical Induction. Example 3.5. Suppose x, y ∈ R and x, y ≥ 0. Then n ∈ N. Proof. Let P (n) be the statement (i) Base Step: P (1) is x+y 2 ≤ ≤ n+1 xn +y n 2 for all xn +y n . 2 x+y 2 , which is true. n n x+y n . Multiplying ≤ x +y 2 2 ≤ (ii) Inductive Step: Suppose x+y 2 x+y n 2 x+y n 2 this by x+y 2 , we find xn + y n x + y 2 2 n+1 n x + x y + xy n + y n+1 4 ≤ = We are hoping (3.1) xn+1 + y n+1 xn+1 + xn y + xy n + y n+1 ≤ . 4 2 This would require Factoring we see 0 ≤ xn+1 − xn y − y n x + y n+1 . xn+1 − xn y − xy n x + y n+1 = (x − y)(xn − y n ). Thus we see inequality (3.1) is satisfied if 0 ≤ (x − y)(xn − y n ). Example 3.4 shows xn ≤ y n for all n if x ≤ y. This implies both terms on the right side of the last inequality are either both positive or both negative and their product is alway non negative. It follows (3.1) is true for all x, y ≥ 0, and so n+1 xn+1 + y n+1 x+y ≤ . 2 2 This is P (n + 1). The result follows from the Principle of Mathematical Induction. Example 3.6. For all n ∈ N n3 − n is divisible by 3. We sometimes express this as 3|(n3 − n). Proof. Let P (n) be the statement 3|(n3 − n). (i) Base Step: P (1) is 3|0. That is, 0 is divisible by 3, which is true. (ii) Inductive Step: Suppose 3|(n3 − n). That is, 3 n3 −n 3 ∈ N. We need to show (n + 1) − (n + 1) ∈ N. 3 Notice (n + 1)3 − (n + 1) = = (n3 + 3n2 + 3n + 1) − (n + 1) (n3 − n) + 3n(n + 1). 32 3. Induction The first term is divisible by 3 by assumption; the second is also divisible by 3. Thus 3|((n + 1)3 − (n + 1)). This is P (n + 1). The result follows from the Principle of Mathematical Induction. Theorem 3.7. Every positive integer is either even or odd. Proof. Let P (n) be the statement every natural number is either even or odd. (i) Base Step: The smallest positive integer is 1, and 1 = 0 · 2 + 1 and so 1 is odd. (ii) Inductive step: Suppose n is either even or odd. If n is even, them n = 2k for some k ∈ N. Then n + 1 = 2k + 1 and n + 1 is odd. If n is odd, n = 2k + 1 for some k ∈ N. Then n + 1 = 2k + 1 + 1 or n + 1 = 2(k + 1). Thus n + 1 is even. This implies n + 1 is either even or odd if n is. The result follows from the Principle of Mathematical Induction. 3.1. Strong Induction Sometimes the Principle of Mathematical Induction is not adequate to show a statement P (n) is true for all n ∈ N. There is another form of induction called Strong Induction. The basic difference is that we assume all P (1), P (2), . . . P (n) to prove P (n + 1) instead of only P (n). Theorem 3.8. (Strong Induction) Suppose P (n) is a statement for each n ∈ N. Moreover, suppose (i) Base Step: P (1) is true. (ii) Inductive Step: for each n ∈ N, P (k), 1 ≤ k ≤ n implies P (n + 1). Then P (n) is true for all n ∈ N. The next example uses both forms of induction. Example 3.9. Every amount of postage of 12� or more can be formed using just 4� and 5� stamps. Proof. We use the Principle of Mathematical Induction. Let P (n) be the statement n is a combination of 4� and 5� stamps. (i) Base Step: Note that 12 = 3 · 4 and so P (12) is true. (ii) Inductive Step: Suppose P (n) is true. Then n = a · 4 + b · 5 for some a, b ∈ N ∪ {0}. If a = 0, then n + 1 = (a − 1) · 4 + (b + 1)5. If a = 0, then n = k · 5 for k ≥ 3. Then n + 1 = (k − 3) · 5 + 4 · 4. Thus P (n + 1) follows. The result follows from the Principle of Mathematical Induction. Alternatively we may use strong induction. To do this we check P (12), . . . P (15) first. We have 12 = 3 · 4, 13 = 2 · 4 + 1 · 5, 14 = 1 · 4 + 2 · 5, and 15 = 3 · 5. This is the base step. 33 3.1. Strong Induction To do the inductive step suppose n ≥ 15 and suppose k = a · 4 + b · 5 for some a, b ∈ N ∪ {0} and for all 12 ≤ k ≤ n. Then n+1 = 1 · 4 + [(n + 1) − 4] = 1 · 4 + (n − 3). Since we assume P (k) for all 12 ≤ k ≤ n, we have n − 3 = a · 4 + b · 4 for some a, b ∈ N ∪ {0}. Thus n+1 = = 1·4+a·4+b·4 (1 + a) · 4 + b · 5, and hence P (12) . . . P (n) implies P (n+1). The result follows from strong induction. We have used the Fundamental Theorem of Arithetic on several occasions. It is now easily justified. Definition 3.10. A natural number n > 1 is prime if it cannot be written as the product of two smaller numbers. Theorem 3.11. (Fundamental Theorem of Aritmetic) Every natural number n ≥ 3 is either prime or is the product of primes. Proof. We use strong induction. Let P (n) be the statement in the theorem. (i) Base Step: Since 2 is prime, P (2) is true. (ii) Inductive Step: Suppose 1, ≤ k ≤ n is prime or the product of primes. If n + 1 is prime, P (n + 1) follows. If n + 1 is not prime, then a, b ∈ N exists so that n + 1 = ab. Moreover, a < n + 1 = ab and b < n + 1 = ab. It follows a > 1 and b > 1. Thus, by assumption, both a and b are either prime or the product of primes. This means ab = n + 1 is the product of primes, and P (n + 1) follows. Another application of the Fundamental Theorem of Arithmetic is that there is no shortage of prime numbers. Theorem 3.12. There are infinitely many prime numbers. Proof. Suppose only a funite number of primes exist, say, {p1 , p2 , . . . , pn }. Set m = p1 p2 . . . , pn + 1. If m is prime m > pi for all 1 ≤ i ≤ n - a contradiction. If m is not prime, m cannot be factored into primes since m/pi ∈ N for all 1 ≤ i ≤ n. This contradicts the fundamental theorem of arithmetic. Remark 3.13. Note that, for there to be an infinite number of primes, we need the fundamental theorem of arithmetic. This requires induction which requires the well-order principle - which is an assumption about the natural numbers. 34 3. Induction 3.2. Justification of Induction We need to justify the Principle of Mathematical Induction by proving Theorem 3.1. To do this we need to make a new assumption about the natural numbers. It turns out that the Principle of Mathematical Induction is equivalent to this new assumption. Theorem 3.14. Let P (n) be a statement for each n ∈ N. The following are equivalent. (a) The Well-Ordering Property: Every nonempty subset of the natural numbers has a least element. (b) The Principle of Mathematical Induction: (i) Base Step: P (1) is true. (ii) Inductive Step: for each n ∈ N, P (n) implies P (n + 1). Then P (n) is true for all n ∈ N. (c) Strong Induction: (i) Base Step: P (1) is true. (ii) Inductive Step: for each n ∈ N, P (k), 1 ≤ k ≤ n implies P (n + 1). Then P (n) is true for all n ∈ N. Proof. Suppose N enjoys the well-ordering property and suppose P (1) and P (n) → P (n + 1) for all n. We prove (b) by contradiction. Suppose P (n) is not true for all n ∈ N. Set E = {n | P (n) is false}. Then E = ∅ and is a subset of the natural numbers. By the well-ordering property there is a least such n which we label n0 . Since P (1) is true, n0 > 1. By construction, P (n0 ) false while is P (n0 − 1) is true. Since P (n − 1) → P (n) for all n, we have P (n0 ) is true. This is a contradiction and the set E must be empty. This proves (b). Next we show (b) implies (c). Suppose P (1) is true and for each n ∈ N, P (k), 1 ≤ k ≤ n implies P (n + 1). Set Q(n) to be the statement P (k) is true for all k ≤ n. We prove Q(n) is true for all n ∈ N by using Part (a). (i) Base Step: Q(1) is the statement P (1) is true, and so Q(1) is true. (ii) Inductive Step: Suppose Q(n). Then P (k) is true for all k ≤ n. By assumption P (n + 1) follows. Thus P (k) is true for all k ≤ n + 1. That is, Q(n + 1) is true. By the Principle of Mathematical Induction, (b), Q(n) is true for all n ∈ N. That is, P (n) is true for all n ∈ N and (c) follows. Finally, suppose (c). We need to show the well-ordering property follows. Let P (n) be the statement “every subset of N containing n has a least element.” We use (c), strong induction, to show P (n) is true for all n ∈ N. (i) Base Step: P (1) means 1 is in the subset. Since 1 is the smallest natural number, any set containing 1 has a least element. Thus P (1) is true. (ii) Inductive Step: Suppose P (k) for 1 ≤ k ≤ n. We need to show P (n + 1) follows. The statement P (n + 1) means every set containing n + 1 has a minimum element. If n + 1 is the minimum, then P (n + 1) is true. If n + 1is not the minimum, then there exists i < n + 1 in the set. Such sets have a 3.2. Justification of Induction 35 minimum (since P (1), . . . , P (n) are assumed true), and therefore P (n + 1) follows. The well-order property follows. 36 3. Induction 3.3. Homework Exercise 3.1. Give a sequence of statements, P (n), for n a natural number such that P (1), P (2), . . . , P (99) are all true but P (100) is false. Make it simple. Exercise 3.2. Suppose a1 = 1, a2 = 8, and an = an−1 + 2an−2 for n ≥ 3. Prove that an = 3 · 2n−1 + 2(−1)n for all n ∈ N. Exercise 3.3. Suppose x1 = 1 and xn = 1 ≤ xn ≤ 3/2, and xn ≤ xn+1 for all n ∈ N. 1 4 (2xn−1 + 3) for all n ≥ 2. Prove Exercise 3.4. Suppose x1 = 3 and xn = 2 − 1/xn−1 for all n ≥ 2. Prove 1 ≤ xn ≤ 3, and xn ≥ xn+1 for all n ∈ N. Exercise 3.5. We say a statement P (n) is eventually true if there exists a N ∈ N such that P (n) is true for all n ≥ N . For each positive real number x determine if xn + x < xn+1 is true or false for all n ∈ N or is eventually true. Exercise 3.6. Prove that 1+ 1 1 1 1 + + ...+ 2 < 2 − 4 9 n n for all n ≥ 2. Exercise 3.7. Let f : R → R satisfy f (x + y) = f (x) + f (y) for all x, y ∈ R. Prove that a) Prove f (0) = 0. b) Prove f (n) = nf (1) for all n ∈ N. Exercise 3.8. Recall a set S of real numbers is convex if, for all x, y ∈ S and all 0 ≤ t ≤ 1, tx + (1 − t)y ∈ S. For every natural number n ≥ 2 suppose S1 , S2 , . . . , Sn are convex, prove S1 ∪ S2 ∪ · · · ∪ Sn is a convex set. Exercise 3.9. Prove that every finite subset of the real numbers has a maximum element. Exercise 3.10. Prove, for all n ≥ 1 1 1 1 1 1 1 1 1 1 − = + − + ···+ . 1 − + − + ··· + 2 3 4 2n − 1 2n n+1 n+2 n+3 2n Exercise 3.11. Prove n n(n + 1) i= 2 i=1 for all n ∈ N by using induction and without using induction. Exercise 3.12. Prove 6|(n3 − n) for all n ∈ N.